The Benzimidazole Derivatives, B1 (N-[(1H-Benzimidazol-2-yl)Methyl]-4-Methoxyaniline) and B8 (N-{4-[(1H-Benzimidazol-2-yl)Methoxy]Phenyl}Acetamide) Attenuate Morphine-Induced Paradoxical Pain in Mice - Idris, Zahida; Abbas, Muzaffar; Nadeem, Humaira; Khan, Arif-ullah (Frontiers in Neuroscience, 2019)
Abstract Despite being routinely used for pain management, opioids use is limited due to adverse effects such as development of tolerance and paradoxical pain including thermal hyperalgesia and mechanical allodynia. Evidence indicates that continued morphine administration causes increased expression of proinflammatory mediators such as tumor necrosis factor-alpha (TNF-α). The objectives of the present study were to determine the effects of B1 (N-[(1H-benzimidazol-2-yl)methyl]-4-methoxyaniline) and B8 (N-{4-[(1H-benzimidazol-2-yl)methoxy]phenyl}acetamide), benzimidazole derivatives, on thermal nociception and mechanical allodynia during repeated morphine (intraperitoneal; 5mg/kg twice daily for 6 days)-induced paradoxical pain and TNF-α expression in spinal cord in mice. Our data indicate that administration of benzimidazole derivatives attenuated morphine-induced thermal hyperalgesia and mechanical allodynia. Benzimidazole derivatives also reduced TNF-α expression in mice. Taken together, these results suggest that benzimidazole derivatives might be useful for the treatment of neuroinflammatory consequences of continued morphine-administration and could be potential drug candidates for the management of opioid-induced paradoxical pain.